PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MATERI PERSAMAAN DASAR AKUNTANSI PADA SISWA KELAS XI DI SMAN 1 SAMBAS - Zainal, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to develop learning media comic matter the fundamental equation accounting to their students class XI at SMA Negeri 1 Sambas and to knows the effectiveness of learning media comic in improving the study results students class X at SMA Negeri Sambas 1. Methods used in this research is research and development (R&D). While for measuring effectiveness of media be held on a students class XI IIS 1 (30 students). For data collection in this research used technique quesioner and tests ( pre-test and post-test ). The data collected from chief and tests analyzed qualitatively. The result of this research is: The effectiveness of learning media comic results of the try out analyzed of tests before and after learning comic media uses, where first trial students passed KKM increased from 43,33% be 93,33%, while the trial two students passed KKM increased from 60% be 93,33%. From the pilot implemented times as many as 2 , it can be argued that the media learning comic matter the fundamental equation of accounting effective in improving the study results students subjects economic class XI SMA Negeri 1 Sambas.Â Keywords: Learning Media, Comic, Fundamental Equation AccountingÂ